2012
DOI: 10.1029/2011jc007599
|View full text |Cite
|
Sign up to set email alerts
|

The solubility of fish‐produced high magnesium calcite in seawater

Abstract: .[1] Fish have been shown to produce high (10 to 48 mol %) magnesium calcite as part of the physiological mechanisms responsible for maintaining salt and water balance. The importance of this source to the marine carbon cycle is only now being considered. In this paper, we report the first measurements of the solubility of this CaCO 3 in seawater. The resulting solubility (pK* sp = 5.89 AE 0.09) is approximately two times higher than aragonite and similar to the high magnesium calcite generated on the Bahamas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…54 mol%) are the highest yet reported in CaCO 3 biominerals. The data presented here corroborate recently published findings of curiously high Mg 2+ levels in fish-produced carbonates of other species1516. The reason for such significant Mg 2+ content in these piscine intestinal deposits may contribute to their ability to remain an amorphous phase throughout their duration in the fish gut.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…54 mol%) are the highest yet reported in CaCO 3 biominerals. The data presented here corroborate recently published findings of curiously high Mg 2+ levels in fish-produced carbonates of other species1516. The reason for such significant Mg 2+ content in these piscine intestinal deposits may contribute to their ability to remain an amorphous phase throughout their duration in the fish gut.…”
Section: Discussionsupporting
confidence: 91%
“…Though previous studies have identified the intestinal deposits as Mg-calcite51516, the widespread distribution of amorphous phases in biological systems1718192021 led us to investigate this possibility in fish-gut carbonates. Amorphous calcium carbonate (ACC) is a unique mineral form produced either as a transient precursor to a final crystallized (calcite or aragonite) structure or as a stable form during the lifetime of the organism2223.…”
mentioning
confidence: 99%
“…Questions thus arise about their stability (Salter et al, 2012), and speculation regarding their dissolution in the upper one kilometre of the pelagic zone (Wilson et al, 2009) is supported by the solubility data of Woosley et al (2012), which indicates a lysocline depth in the North Atlantic of approximately 550 m for highMg calcite fish-derived carbonates. However, since periplatform deposits on the leeward slopes of the GBB commonly begin at depths of 140 to 180 m (Wilber et al, 1990), and because lysocline depths around the Bahamas are thought to be substantially depressed relative to those of the North Atlantic (Droxler et al, 1988), it is highly plausible that fish-derived carbonates will resist dissolution and may accumulate at the surfaces of periplatform deposits.…”
Section: )mentioning
confidence: 98%
“…In particular, the solubility, rate, and mechanisms of calcite dissolution have been extensively studied (e.g., Plummer and Wigley 1976;Sjöberg 1976;Plummer et al 1978;Rickard and Sjoeberg 1983;Arakaki and Mucci 1995;Hales and Emerson 1997). Fewer studies have attempted to investigate similar properties for biogenic carbonates, and only a fraction of these studies have attempted to characterize these properties in natural seawater and under conditions typically observed in the natural environment (e.g., Keir 1980;Morse 1984, 1985;Woosley et al 2012;Yamamoto et al 2012). Many experiments with biogenic carbonate substrates have been done in pure water (Chou et al 1989;Svensson and Dreybrodt 1992;Cubillas et al 2005), with samples that have not been ultrasonically cleaned to remove submicron particles (Keir 1980), with calcite powders or very small grain sizes (Sjöberg 1976;Busenberg and Plummer 1986) and/or at seawater pH levels and saturation states far from equilibrium and much lower than conditions commonly observed in the shallow marine environment (Walter and Morse 1985;Cubillas et al 2005).…”
Section: Introductionmentioning
confidence: 99%